THE IMPORTANCE AND PROSPECTS OF HUMANITIES IN EDUCATION (International Conference on Educational Discoveries and Humanities, 2025)
In the theory and practice of indigenous education, there is a shift from a subject-oriented paradigm to a humanitarian paradigm. The main educational instruction is the integrity of education based on the study of the individual, his real "human" qualities, subjective methods of assimilation (assimilation) of culture. Modern pedagogical practice is increasingly faced with the problems of alienating students from education . Students feel excluded from the learning process and from understanding the role and meaning of education in their lives.A more humanistic education deals with these problems. A distinctive feature of humanitarian education is that it is focused on the "inner" person, on the subjective reality of a specific "empirical" (AB Orlov) person. We mean liberal education, which is not limited to the study of certain subjects. We are talking about education in the context of humanitarian-anthropological approach. In this case, the focus is on the whole person.